Pengaruh Terapi Akupunktur Kombinasi Titik Lokal Dan Titik Telinga Endokrin Terhadap Penurunan Derajat Lesi Akne Vulgaris Remaja Peunayong, Aceh Besar - Utami Pangestu; Ayunda Prisilia K.N; Maria, Tria Zuruna (Teewan Solutions, 2024)
Background: Acne is a skin disease, in form of chronic inflammation of sebaceous gland, which is indicated by comedo, nodule, pustule even cyst. This disease is caused by the increase of oil production on sebaceous gland due to the effect of sex hormone, stress, the decrease of body immunity and infestation of Propionibacterium acnes. Time and Place: This research is conducted on December 2023, Peunayong, Aceh Besar which suffer from acne. Methods: This study is a pre-experimental design with one group pretest-postest with 20 samples of 20 teenagers in Peunayong, Aceh Besar who met the inclusion criteria. Analyzes using Wilcoxon univariat and bivariat analyze. Result: Reduction of grade lesions p = 0,000 < 0,05, Conclusion : Acupuncture using combination local point and Endocrine auricular point is effective in lowering acne lesion count.